A novel indicator to assess PIT tag retention in an aquatic amphibian: impact of body size - Jacob M. Hutton; Adrian D. Macedo; Jason L. Brown; Robin W. Warne (Animal Biotelemetry, 2024)
Abstract The comprehensive study of organisms is often hindered by the difficulty of consistently capturing, detecting, and tracking all life stages and age classes. This challenge is particularly pronounced for aquatic amphibians such as Siren intermedia (lesser siren), which can aestivate underground in dry burrows during extended droughts. In addition, obtaining year-round data on the habitat use, occupancy, and movement ecology of S. intermedia is notably difficult due to their cryptic nature, mobility, aestivation behaviors, trap-shy habits, and the impracticality of outfitting hatchlings and small juveniles with telemetry devices like subcutaneous Passive Integrated Transponder (PIT) tags. Moreover, there is the lack of a non-physical method to distinguish retained tags from those that have been dropped. In this study, we developed a novel indicator to assess the field retention status of PIT tags inserted into the tail tissue of S. intermedia. This was achieved by analyzing individual spatial redetection patterns of 8- and 12-mm PIT tags inserted into juveniles and adults, respectively, over 2 years in a remnant Cypress–Tupelo swamp wetland complex in southern Illinois, using systematic dipnetting, trapping, and PIT scanning telemetry surveys. Tags were considered dropped if the average distance between subsequent scanned PIT detections after the first redetection was ≤ 5 m and if the distance between the second detection and final redetection location was also ≤ 5 m. We then examined PIT tag retention in relation to initial body size and marking parameters. Ultimately, 29% of the 8-mm PIT tags initially injected into juveniles with tail lengths (Tail) 46–84 mm were redetected at least once. Using our spatial–temporal PIT telemetry indicator, we found that 45% of the redetected PIT tags had been dropped by juveniles. In contrast, all three of the 12-mm tagged adults were redetected at least once, with movement patterns indicative of tag retention. Our findings suggest that 8-mm PIT tags are likely to be expelled from juvenile S. intermedia with a mean ± standard deviation (SD) Tail of 50.2 ± 2.8 mm. This study underscores the importance of determining appropriate size requirements and cutoffs for effective telemetry device application across different age classes of a species.